Industry Involvement In Undergraduate Research Project For Chemical Engineering (Biotechnology) Programme - N., Zainol; Sumaiya, Zainal Abidin; Noraziah, Abu Yazid (2014)

(untitled)
This paper reported on industry involvement in Undergraduate Research Project (URP) course. During the final year of study, Chemical Engineering (Biotechnology) (BKB) students were required to conduct a final year project. Undergraduate Research Project (URP) was divided into two which were URP I and URP II. In URP I, students have to prepare a research proposal and URP II was the continuation of URP I. In URP II the students were required to conduct the research and produce the dissertation. Rubrics for each evaluation have been developed to clearly define the assessments. In order to ensure a strong connection between students, staff and industry, BKB students were required to have at least 15% industrially linked/based URP topics. Starting from 2012, the faculty has invited external examiners from research institution and industries to assess students during their URP II presentation seminar. The presentation seminar was successfully conducted with the involvement of 14 industrial academic panels. The panels came from various industries, research institutes and consultation companies such as Petronas, MTBE Malaysia, Bio tropics Malaysia, MOX Gases, FRIM and Sime Darby. Their recommendations and suggestions during the presentation projects have benefited all students and lecturer towards improving their research works. Other than that, the requirement to have at least 15% industrially linked URP topics has strengthened the relationship between the faculty and industry. In addition, several URP projects has been sent for research exhibition, internal and externally.